1973
DOI: 10.1136/gut.14.2.133
|View full text |Cite
|
Sign up to set email alerts
|

Mobilization of tissue kallikrein in inflammatory disease of the colon

Abstract: SUMMARY Colonic tissue was taken at operation from 10 patients with active ulcerative colitis and three patients with uncomplicated diverticular disease but with severe symptoms. Levels of kininogen, kallikrein, and kallikrein precursor were measured in blood-free tissue samples. In normal colon tissue a kininogen occurred in the muscle and none was detected in the mucosa. Kallikrein and its precursor were found in mucosa but not in muscle. In acutely inflamed tissue from ulcerative colitis patients relatively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
1
1

Year Published

1986
1986
2011
2011

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(25 citation statements)
references
References 17 publications
0
23
1
1
Order By: Relevance
“…Zeitlin and Smith reported relatively high levels of active tissue kallikrein in acutely inflamed tissue from UC patients, suggesting that kinins can be generated from lowmolecular-weight kininogen during active human disease (12). Furthermore, the involvement of the kallikrein-kinin system in the development of experimental IBD models that mimic human Crohn's disease was also reported (8,9,35).…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…Zeitlin and Smith reported relatively high levels of active tissue kallikrein in acutely inflamed tissue from UC patients, suggesting that kinins can be generated from lowmolecular-weight kininogen during active human disease (12). Furthermore, the involvement of the kallikrein-kinin system in the development of experimental IBD models that mimic human Crohn's disease was also reported (8,9,35).…”
Section: Discussionmentioning
confidence: 94%
“…1), in the presence of DSS, kinin generation occurred in plasma taken from SD and BN-Ki, but not in that from BN-Ka. In contrast, the epithelial cells of the intestine were reported to contain the tissue kallikrein (12,22,43,44). Once the damage to the intestinal mucosa is induced, the tissue kallikrein may be released from the epithelial cells (43).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Long time ago only one study (Zeitlin & Smith, 1973) reported the presence of tissue kallikrein in normal human colon and a higher concentration in the inflamed colon of patients with UC. In rat model of PG -APS stimulated chronic inflammation we have shown that the normal location of ITK was the goblet cells and substantial amounts of ITK were present in the macrophages of the granulomas found in the submucosa indicating that ITK is present at the site of inflammation .…”
Section: Intestinal Tissue Kallikreinmentioning
confidence: 99%